Analysis of Recurrent Positive COVID-19 Patients in A Hospital - Ensar Durmus; Fatih Guneysu (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
The studies about COVID-19 began to show that people who have already had COVID-19 were re-admitted to the hospital due to COVID-19 positivity. This study aims to identify recurrent positive patients and the demographic characteristics of these patients. The number of recurrent COVID-19 positive patients was 190. Of these patients, 97 (51.1%) were male, the average age was 43.98 years (±16.3), 147 (77.4%) were never hospitalized, Of the hospitalized patients, 28 (65.1%) were male and the average age of the inpatients was 54.67 years (±16.15). Looking at the duration of hospital stay of the inpatients, it was observed that the average was 11.16 days (±8.9). A positive correlation was found between the age of the patients and the duration of their hospital stay (r=0.386). The average time between the two positives was 52.92 days. Patients who have a recurrent positive result usually survive the disease with outpatient treatment for their mild illness. Hospitalization rates of male patients were higher than those of females, and the duration of hospital stay was found to increase as the age of the patients increases.